1995
DOI: 10.1006/viro.1995.1463
|View full text |Cite
|
Sign up to set email alerts
|

Core Antigen Mutations of Human Hepatitis B Virus in Hepatomas Accumulate in MHC Class II-Restricted T Cell Epitopes

Abstract: Despite the extensive molecular information on serum-derived human hepatitis B viruses (HBV), liver-derived replicative HBV genomes have remained largely uninvestigated. We have examined the sequences of the entire core antigen (nucleocapsid) of liver-derived HBVs in 15 different hepatoma patients. Bona fide mutations, rather than subtype polymorphism, have been identified based on the high-frequency occurrence of structural differences from wild type at the highly evolutionarily conserved positions, instead o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 0 publications
8
93
0
Order By: Relevance
“…These BCP mutations may be detected with or without PC mutations (17)(18)(19). Core mutations, particularly amino acid (aa) at position 130 exposed on the surface of mature HBeAg, were observed in the course of disease progression and accumulate in the B-and T-cell epitopes (20,21). These findings emphasize the possibility that the mutations in the T-or B-cell epitopes exert a significant effect on T-cell function or subsequent cytokine release and on the association between the host immunological reaction and viral persistence.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…These BCP mutations may be detected with or without PC mutations (17)(18)(19). Core mutations, particularly amino acid (aa) at position 130 exposed on the surface of mature HBeAg, were observed in the course of disease progression and accumulate in the B-and T-cell epitopes (20,21). These findings emphasize the possibility that the mutations in the T-or B-cell epitopes exert a significant effect on T-cell function or subsequent cytokine release and on the association between the host immunological reaction and viral persistence.…”
Section: Introductionmentioning
confidence: 91%
“…The inflammatory activity produced by viral adaptive mechanisms may persist in up to 15% of cases, leading to the development of cirrhosis (48). A previous study by Hosono et al (20) suggested that core mutations in HBV accumulated more errors in tumors compared to non-tumors. The aa 120-140 in the core region exposed on the surface of mature HBeAg and HBcAg are related to the recognition of helper T cells (49)(50)(51) and the immunodominant B-cell recognition sites within the HBcAg have also been found around residues 126-135 (45,46).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…The precore-Cys-23 was found to be highly conserved in Taiwanese hepatomas [16] while in Italian hepatomas this Cys could be changed [108,109].…”
Section: Mutations Of the Precore-regionmentioning
confidence: 99%
“…8 As shown in Figure 2, there were 5 "hot-spots" mutations in the core region, which were all located in the B cell epitopes (codons 76 -89, 130 -135, 146 -159) and T cell epitopes (61-85, 81-105, 117-131). 9 Furthermore, 2 isolates showed a stop-codon mutation in the precore region, which abolished HBeAg expression.…”
Section: Mutations In Hbv Coding Regionsmentioning
confidence: 99%